1997
DOI: 10.1177/096120339700600903
|View full text |Cite
|
Sign up to set email alerts
|

Occasional Series—Lupus Around the World Systemic lupus erythematosus in India

Abstract: The first case of systemic lupus erythematosus (SLE) was reported from India in 1995 followed by two more case reports and further, a series of eight cases, till 1969. Since the establishment of a clinical immunology laboratory at a major teaching institution in New Delhi in 1968, SLE was extensively studied and reported from that centre. From mid-1980 onwards several other centres in different regions in India including Chennai (old name Madras), Mumbai (old name Bombay), Calcutta and Hydrabad, also published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 49 publications
6
16
3
Order By: Relevance
“…Among other Asian populations, the frequency of aPL varies between 13% to 71% (Table 9). 34–42 This was similar to Western SLE cohorts which reported positive aPL in 25–50% of their SLE patients, and thrombosis in 40–50% of those with aPL 43 . In the Asian studies, the frequency of SAPS in SLE appears to be much lower in the Far‐eastern patients (< 10%), while among the Middle‐eastern population, particularly in Kuwait, it was high (> 20%) 41,42 .…”
Section: Discussionsupporting
confidence: 79%
“…Among other Asian populations, the frequency of aPL varies between 13% to 71% (Table 9). 34–42 This was similar to Western SLE cohorts which reported positive aPL in 25–50% of their SLE patients, and thrombosis in 40–50% of those with aPL 43 . In the Asian studies, the frequency of SAPS in SLE appears to be much lower in the Far‐eastern patients (< 10%), while among the Middle‐eastern population, particularly in Kuwait, it was high (> 20%) 41,42 .…”
Section: Discussionsupporting
confidence: 79%
“…The overall prevalence rate of lupus nephritis was higher in the current study compared to notable surveys [22,23]. It is noteworthy that previous studies have suggested that the highest rate of renal involvement in the world (73%) was found in Indo-Asians [16,24].…”
Section: Discussion ___________________________contrasting
confidence: 67%
“…There are limited studies on Indian SLE patients. Although the prevalence of SLE in India is rare (3/100,000) [3], the survival rates of these patients (70% at 5 years, 50% at 10 years) are very low compared to Western cohorts [4,5]. Several factors are thought to be responsible for poor survival rates, the most important being delayed diagnosis [6].…”
Section: Introductionmentioning
confidence: 99%